Effect of short-circuit degradation on the remaining useful lifetime of SiC MOSFETs and its failure analysis. (November 2020) - Du, H.; Letz, S.; Baker, N.; Goetz, T.; Iannuzzo, F.; Schletz, A.
Abstract: When the SiC MOSFET works in the normal operating conditions, its remaining useful lifetime used to be estimated based on the monitored parameters and the lifetime model derived from accelerated tests. In this case, the degradation caused by abnormal events has not been considered. Therefore, it makes sense to investigate the effect of short-circuit degradation on the remaining useful lifetime of SiC MOSFETs. A different number of repetitive short-circuit events have been introduced into the accelerated power cycling tests to assess the impact. The experimental results indicate a gate degradation with the increasing number of short-circuit repetitions, which leads to higher conduction loss and earlier failure. Further failure analysis is achieved by performing lock-in thermography, scanning electron microscopy, and focused ion beam. Highlights: The mixed power cycling tests with different short-circuit stress are performed on 1000-V 22-A SiC MOSFETs. A larger number of short-circuit repetitions induce higher gate leakage current, temperature swing and earlier failure. A dielectric silicon dioxide crack is observed, which may form the higher gate leakage current. The inhomogeneity of aluminium grains size might be caused by a strong vertical temperature gradient during the test.